Expression of Wilms tumor gene protein (WT1) in different histologic subtypes of ovarian carcinoma - Hossain, M. Zahid; Naznin, Mahmuda; Majumder, Swapna; Imran, Zahir Al; Rabiul Haque, Mohammad (International Journal of Advances in Medicine, 2023)
Background: Ovarian carcinoma is the seventh most common cancer among women worldwide and the eighth leading cause of death. Ovarian cancer develops in the ovary’s tissues. Methods: This cross-sectional descriptive study was carried out at the Department of Pathology, RMC and Department of Pathology, BSMMU, Dhaka, Bangladesh from July 2019 to June 2021 carried out with 31 histopathologically confirmed ovarian carcinomas. All cases were subjected to WT1 immunostaining followed by histopathological examination. The collected data were analyzed using Statistical Package for Social Sciences (SPSS) software, version-23.0. The ethical clearance of this study was obtained from the Institutional Review Board (IRB) of Rajshahi, Medical College, Rajshahi, Bangladesh. Results: A total of 31 histopathologically confirmed ovarian carcinoma patients were included in this cross-sectional descriptive study. All cases were subjected to WT1 immunostaining followed by histopathological examination. The age of the study sample ranged from 20 to 75 years. The mean age of the respondent was 45.10±13.78 years. According to the histologic subtypes, WT1 was mainly expressed in serous carcinoma. All the serous carcinoma (16/16) showed a positive reaction for WT1. Among them, 14 cases (87.5%) showed >50% (3+) WT1 score and two (2) cases (12.5%) showed 11% to 50 % (2+) scores. Regarding endometrioid carcinoma four (4) (66.6%) of six (6) were negative whereas one (1) (16.6%) showed 1%-10% (1+) and one (1) (16.6%) showed 11%-50% (2+) WT1 scores. All the mucinous (4/4) and all the clear cell carcinoma (3/3) were negative with less than 1 % of the tumor cells stained two (2) cases of undifferentiated carcinoma were also negative. There was a significant relation between WT1 expression and different histologic subtypes of epithelial ovarian carcinoma with a p value of 0.001 (p<0.05). Conclusions: WT1 can be applied by both the histopathologist and clinician as an effective marker regarding diagnosis and patient management.